Christian biblical ethics: the application of biblical norms to today - Patrick J. Hartin (Koers : Bulletin for Christian Scholarship, 1991)
Christian theologians give many different interpretations to the Scriptures, particularly with regard to their ethical perspectives and their application to the present. An examination and criticism of various approaches adopted at present to the ethical dimension of the Scriptures is undertaken. A distinction is made between the revealed and lasting message of the Scriptitres and the message that is conditioned by culture and hence subject to change. Using the thought of Ricoeur and Hauerwas an approach is presented which attempts to do justice to the twofold polarity of the worid of the Bible and the world of today. In order to preserve a scenario of concreteness, attention is given to one practical example, namely the issue of homosexuality. After investigating the Scriptural approach to this question, an attempt is made to see how this issue can be viewed from a Christian perspective in the context of the present world.